1996
DOI: 10.1017/s0376892900038510
|View full text |Cite
|
Sign up to set email alerts
|

The mercury problem and diets in the Brazilian Amazon: planning a solution

Abstract: SummaryIn order to determine whether mercury from distant goldmining affected health in the districts of lranduba and Barreirinha, Amazonas State, Brazil, mercury in the scalp hair of 101 peasants (39 males and 62 females) was determined by cold vapour atomic absorption. In both areas fish is the major source of dietary protein. The average hair mercury content was 38.6 ppm (1SD = 14.1) in Barreirinha, where the diet contains a high proportion of carnivorous fish, and 5.6 ppm (1SD = 3.1) in Iranduba, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…While the authors point to gold mining in the Upper Negro River (Colombian Amazon) as the probable source, recent biogeochemical studies have shown the important impact of naturally occurring Hg in this basin 14,61,62 , concluding that Hg leaching from soils constitutes the largest regional reservoir of this metal 14 . These findings are supported by studies analyzing environmental determinants of Hg levels in fish as well as dietary human exposure, all of which indicate that fish and human Hg levels in the Negro River Basin are strongly influenced by naturally high background Hg levels 37,63,64 . However, it is difficult to ascertain the true source of exposure (which may not be unique) for each community, and the variation in results from communities in the Negro River basin might depend upon where sampling was performed.…”
Section: Mercury Sources Fishing Resources and Bioindicators Of Expmentioning
confidence: 62%
See 2 more Smart Citations
“…While the authors point to gold mining in the Upper Negro River (Colombian Amazon) as the probable source, recent biogeochemical studies have shown the important impact of naturally occurring Hg in this basin 14,61,62 , concluding that Hg leaching from soils constitutes the largest regional reservoir of this metal 14 . These findings are supported by studies analyzing environmental determinants of Hg levels in fish as well as dietary human exposure, all of which indicate that fish and human Hg levels in the Negro River Basin are strongly influenced by naturally high background Hg levels 37,63,64 . However, it is difficult to ascertain the true source of exposure (which may not be unique) for each community, and the variation in results from communities in the Negro River basin might depend upon where sampling was performed.…”
Section: Mercury Sources Fishing Resources and Bioindicators Of Expmentioning
confidence: 62%
“…No matter what the environmental source, fish-eating practices are the most important predictor of Hg exposure in most areas of the Amazon, explaining a substantial proportion of the variation of total and methyl-Hg concentrations in both blood and hair. Based on these bioindicators, as well as Hg measurements in fish tissue, many studies in the Amazon have associated Hg exposure with fish consumption 4,26,27,32,33,37,39,45,46,65,66,67,68,69,70,71,72,73,74 , especially for members of fishing families 75,76,77 . These studies support the universal observation that fish consumption constitutes the most important source of Hg exposure worldwide 22,25 .…”
Section: Mercury Sources Fishing Resources and Bioindicators Of Expmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian Amazon, mercury contamination of fish can occur as a result of both natural biogeochemical processes and gold-mining activities (Pfeiffer and Lacerda, 1988;Eve et al, 1996;Lechler et al, 2000). Human mercury contamination results primarily from fish consumption because fish not only absorb methylmercury (MeHg) from the water throughout their life but also convert inorganic Hg +2 to methylmercury through biomethylation occurring in their body.…”
Section: Introductionmentioning
confidence: 99%
“…The median values for total Hg and MeHg interval (in % of total Hg) in hair samples for the Mercury and methylmercury concentration assessment in children's hair from Manaus, Amazonas State, Brazil be assumed that low income communities such as Indian and riverine populations have as their primary protein source, fish. cited that among fish consumers, riparian communities present the highest degree of exposure, with mean hair-Hg as high as 38.6 ± 14.4 mg kg -1 (Eve et al, 1996) and 65 ± 58 mg kg -1 (Leino et al, 1996). Overall, urban fish-consumers are the least exposed, presenting mean hair-Hg levels of 2.4 mg kg -1 , 2 mg kg -1 (Passos et al 2003), and 1.9 mg kg -1 (Webb et al 2004).…”
Section: Resultsmentioning
confidence: 99%